Screening Tuberkulosis pada Pasien Diabetes Mellitus untuk Meningkatkan Case Notification Rate di Kota Denpasar - Putu Ika Farmani (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: Case Notifivation Rate (CNR) is one of survailance tuberculosis (TB) program goals indicator in public health centre which is indicate the discovery rate of new tuberculosis patients in society, however Denpasar City TB CNR in last three years (2011-2013) tends to decrease. Aims study: for implementation and evaluation TB case screening activities in patients with DM (Diabetes Melitus) in Denpasar Public Health Centres. Method: Implementation was carried out by applying the TB screening form to 26 DM patients in West Denpasar Public Health Centre II and followed by sputum examination in laboratory. Furthermore sceening activities evaluation was held based on surveillance arttributes which was next analyzed qualitatively and quantitatively. Result and discussion: Result showed 7.6% (2) had been infected with tuberculosis: 57.6% (5) with TB symtoms and 50% (13) were reffered for sputum examination. As many 10 peoples felt disposed to take the sputum examination, with 8 peoples registered to laboratory, 6 peoples gave up the sputum, and 1 person positive TB. Screening evaluation result: the proportion of TB positive cases among those who were examided was 16.7%. Farther, we got the estimation of CNR increase in 2014 amount 34.37% by extrapolationg the 2013 CNR.Conclusion: TB case screening activities in DM patients potentially could increase the CNR TB goals in Denpasar City and expected could be developed in all Denpasar Public Health Centres, especially for the Public Health Centres with high DM cases.